Pengaruh Pertumbuhan Ekonomi, Ketimpangan Pendapatan, Investasi Domestik, Pendidikan, Swamedikasi, dan Pengangguran Terbuka terhadap Kedalaman Kemiskinan di Indonesia - Saputri, Kurnia; Udjianto, Didit Welly (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2023)
Poverty is a human condition that cannot buy basic needs using their income. This research will discuss the factors that affect the poverty gap, such as economic growth, income inequality, domestic investment, education, self-medication, and the open unemployment, and discuss how the direction of influence on the level of poverty gap. In this study, panel data regression analysis was used, with the object of research being 34 provinces in Indonesia and the research period from 2017 to 2021. The results showed that the best model was Random Effect. Based on the regression results, it was known that economic growth and education had a negative and significant effect on the level of poverty gap. Meanwhile, the open unemployment variable had a positive and significant effect on the poverty gap.